Improving the Scientific Literacy of Food Engineering Students in Electrohydrodynamic Processing by Means of Zein Solutions - Sergio Torres-Giner; Alberto Yuste; Chelo González-Martínez (MDPI AG, 2022)
Electrohydrodynamic processing (EHDP) has revolutionized nanotechnology since it is a simple method for developing microstructures and nanostructures from a wide range of polymer solutions using the application of high voltages. However, EHDP has scarcely been introduced into food engineering courses at any educational level, whereas it is fundamental for professionals in the discipline. The present educational article aims to introduce, for the first time, the basis of the EHDP technology and its management to students in postgraduate courses for food emulsion and related disciplines. To this end, the document reports the step-by-step preparation of zein solutions in aqueous ethanol with varying weight protein contents and the characterization of such solutions in terms of their density, viscosity, surface tension, and conductivity. Then, the methodology also describes the processability of the resultant zein solutions using EHDP. Process parameters, including applied voltage, flow-rate, and tip-to-collector distance, were studied to optimize proper deposition of zein materials in the form of a wide range of morphologies, from nanobeads to microfibers. The attained results were related to the zein solution properties and processing conditions, which can help to understand the effect of these parameters and exemplify the potential of this technology to develop novel ultrathin food hydrocolloid structures. Finally, the application of this methodology was assessed through online surveys taken during food engineering courses and findings indicate that postgraduate students appreciate the exposure provided by the experimental activities, particularly to achieve familiarity with food hydrocolloid solutions and scientific literacy in the EHDP technology.